2008
DOI: 10.1158/1078-0432.ccr-07-4711
|View full text |Cite
|
Sign up to set email alerts
|

Local Administration of PF-3512676 CpG-B Instigates Tumor-Specific CD8+ T-Cell Reactivity in Melanoma Patients

Abstract: Purpose: Impaired immune effector functions in the melanoma sentinel lymph node (SLN) may allow for early metastatic events. Local administration of PF-3512676 (formerly known as CpG 7909) has shown immunostimulatory effects of both dendritic cell and T-cell subsets in the melanoma SLN. Here, we set out to ascertain whether these PF-3512676-induced immunostimulatory effects translate into higher frequencies of melanoma-specific CD8 + Tcells. Experimental Design: Twenty-four stage I to III melanoma patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 46 publications
4
98
0
Order By: Relevance
“…Furthermore, neither treatment with polyI:polyC nor with Imiquimod could break established tolerance in K5-Ova/K5-CreER mice (data not shown). This was surprising because we and others have previously shown that Imiquimod and CpG are potent immune stimulators capable of inducing efficient immune responses against melanoma in the skin (45)(46)(47)(48). We speculated that this lack of immune stimulation was due to weak cross-presentation, as indicated by the poor Ag presentation in skin draining LN of TXtreated 26K5-Ova/K5-CreER mice in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, neither treatment with polyI:polyC nor with Imiquimod could break established tolerance in K5-Ova/K5-CreER mice (data not shown). This was surprising because we and others have previously shown that Imiquimod and CpG are potent immune stimulators capable of inducing efficient immune responses against melanoma in the skin (45)(46)(47)(48). We speculated that this lack of immune stimulation was due to weak cross-presentation, as indicated by the poor Ag presentation in skin draining LN of TXtreated 26K5-Ova/K5-CreER mice in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…The intact ability of melanoma-infiltrating pDCs to respond to TLRL stimulation is consistent with the potent antitumor responses following imiquimod (TLR7-L) therapy in patients with melanoma (46)(47)(48) or after CpG (TLR9-L; refs. 14, 15) treatment, both of which involved the recruitment and activation of pDCs (16,17,(46)(47)(48). Despite the role of pDCs on tumor progression under steady state conditions, remobilization of pDCs using TLR agonists represents a promising means to achieve melanoma tumor control by reversing the functional hijack of pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pDCs play a pivotal role in antitumor immunity through their ability to process and cross-present tumor antigens to T cells (8), and subsequently induce adaptive immune responses (9). In the context of melanoma, pDCs have been shown to prime functional immune responses (9)(10)(11), display direct cytotoxic activity towards tumor cells through TRAIL expression (12) or lysozyme secretion (13), or once activated, potentially achieve melanoma tumor control through efficient priming of antitumor responses (14)(15)(16)(17). Infiltration of tumors by pDCs has been found in many types of cancers, yet associated with poor prognosis, especially in ovarian (18) and breast cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 We have used this methodology to study the in vivo effects of immune modulators such as the CpG-B TLR9-ligand PF-3512676 and GM-CSF on DC and T-cell subsets in the SLN. [18][19][20][21] In the context of 3 separate clinical phase 2 trials, we have collected a sizeable number of SLNs from untreated or saline placeboadministered melanoma patients, from which phenotypic DC data were obtained through multiparameter flow cytometric analysis and of which viable cells were cryopreserved for further functional analysis. From these, we have selected tumor-negative SLNs from Stage I-II melanoma patients, which were removed 1-2 months after excision of the primary melanoma, to perform an in-depth analysis of cDC subsets in steadystate skin-draining LNs.…”
mentioning
confidence: 99%